Colombian Truth Commission: Switzerland retains archive copy - The Federal Council (Confédération Suisse - Conseil fédéral, 2023)
At its meeting on 21 June, the Federal Council approved an agreement to retain a digital backup copy of the archives of the Colombian Truth Commission. Dealing with the past is a key focus area of Switzerland's long-standing peace policy work in Colombia. In safeguarding such sensitive data, Switzerland is supporting the peace process in the long term.
Keywords: 2023-06 June